An Analytical Study Of The Maqāṣid Al-Mukallaf Perspective On The Use Of Stem Cells For Beauty Enhancement - Mutmainnah, Iin Mutmainnah (Al-'Adl, 2026)
This study examines the use of stem cells for aesthetic purposes through the lens of maqashid al-mukallaf, which emphasizes the moral and legal responsibility of Muslims within the framework of maqashid al-shari‘ah. This research employs a qualitative, normative-theological, and maqashidi approach. The findings indicate that stem cell applications for cosmetic enhancement are permissible when aimed at restoring natural bodily functions and derived from lawful sources. However, using stem cells merely to alter God’s creation or for excessive beautification contradicts the objectives of Sharia. The study highlights the moral awareness required of the mukallaf to balance medical benefit with ethical restraint under Islamic law.